The Influence of The Green Learning Method (GeLem) on Students' Environmental Literacy related Biodiversity - Riani, Aisyah (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2023)
This study aims to determine the effect of Green Learning Method (GeLem) learning on students' environmental literacy based on student learning outcomes on biodiversity material in class X Senior High School Prayatna Medan academic year 2021/2022. This research is a quantitative research with a quasi-experimental research type. In this study the sampling technique was carried out by total sampling. The sample in this study consisted of students in class X IPA 2 as the experimental class and students in class X IPA 3 as the control class. The instrument used in the study was an essay test sheet to measure student learning outcomes on biodiversity material. In this study it was found that there was an effect of the green learning method on students' environmental literacy based on student learning outcomes, obtained an average score of 62.7 (pre-test) and 82.5 (post-test) with a percentage of 56.1% which was categorized as effective enough. It can be concluded, there is an effect of the green learning method on students' environmental literacy based on student learning outcomes on biodiversity material.